SCIENTIFIC PRODUCTION ABOUT THE LATE DIAGNOSIS OF BREAST CANCER IN YOUNG WOMEN: BIBLIOGRAPHICAL REVIEW STUDY - Kelly Araújo Silva Melo, Geni; Paula Santos e Silva, Ana (Health and Society, 2023)
The objective of this study is to: Analyze scientific productions on the diagnosis of breast cancer in young women. This study is of the bibliographic modality, with a qualitative, descriptive and exploratory approach. The bibliographic study occurs from a data survey, which uses some instruments, such as: books, scientific articles, theses, dissertations, legislation and other published sources. 10 scientific articles were used, unifying the descriptors and also the information found. Knowing that breast cancer is common in women over 50 years of age, as seen in the results found, there are studies that prove the increase in cases in young women, which raises awareness about this very important topic. In this way, many changes can occur in a woman’s life that lead to the occurrence in youth, and faced with so many demands, in addition to factors related to family, work, emotional, social and food activities, there is difficulty in diagnosing, making it late.